Relationships Between Rearing Enrichments, Range Use, and an Environmental Stressor for Free-Range Laying Hen Welfare - Bari, Md Saiful; Downing, Jeff A.; Dyall, Tim R.; Lee, Caroline; Campbell, Dana L. M. (Frontiers in Veterinary Science, 2020)
Enrichments during pullet rearing may improve adaptation and welfare of hens as they move from indoor rearing to a free-range system. Individual variation in outdoor ranging may also affect welfare. This study assessed the effects of rearing enrichments and an imposed environmental stressor on hen welfare and egg quality along with the association of welfare with ranging. Hy-Line Brown® chicks (n = 1386) were reared indoors until 16 weeks with 3 enrichment treatments including a ‘control’ group with standard floor litter, a ‘novelty’ group that received novel objects that were changed weekly, and a ‘structural’ group with H-shaped perching structures. Pullets were then moved to a free-range system with three replicates of each rearing treatment. Daily ranging was individually-tracked from 25 to 64 weeks via radio-frequency identification technology. Individual hen welfare assessments were performed at 25, 33, 43, 56 and 64 weeks and correlated with ranging time prior to these dates. At 44 weeks the range area was reduced by 80% for 11 days to induce stress. Changes in ranging behavior, albumen corticosterone concentrations and egg quality were evaluated. GLMMs showed significant interactions between hen age and rearing treatment for live weight, number of comb wounds, plumage coverage and toenail length (P < 0.006) with the enriched hens showing more consistent live weight at the later ages, fewer comb wounds at 33 weeks and better plumage coverage at the later ages, whereas the structural hens had shorter toenails as age increased. Plumage coverage showed a positive relationship with range use across most age points (P < 0.0001). Hens reduced ranging time following the imposed stressor (P < 0.0001) but increased their number of visits with the lowest increase by the structural hens (P = 0.03). Significant interactions between rearing treatment and stressor for albumen corticosterone concentrations showed the structural hens decreased concentrations immediately post-stress, but the control and novelty groups increased (P < 0.006). The stressor increased or decreased values of most egg quality parameters across all rearing groups (all P ≤ 0.004). Overall, provision of rearing enrichments and greater range use may have positive impacts on hen welfare.